2011
DOI: 10.1080/14926156.2011.570476
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Concept Consistency

Abstract: This paper investigates the extent to which undergraduates consistently use a single mechanism as a basis for classifying mathematical objects. We argue that the concept image/concept definition distinction focuses on whether students use an accepted definition, but does not necessarily capture the more basic notion that there should be a fixed basis for classification. We examine students' classification of real sequences before and after exposure to definitions of 'increasing' and 'decreasing'; we develop an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…First, Alcock and Simpson (2011) found that in relation to these concepts, students classified sequences in a wide variety of ways. Second, their formal definitions are relatively straightforward compared with many definitions at this level (each has only one quantifier and one relation), so poor classifications are less likely to result from failing to understand the definitions (Dubinsky & Yiparaki, 2000).…”
Section: Task Sequencing In Definition-based Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…First, Alcock and Simpson (2011) found that in relation to these concepts, students classified sequences in a wide variety of ways. Second, their formal definitions are relatively straightforward compared with many definitions at this level (each has only one quantifier and one relation), so poor classifications are less likely to result from failing to understand the definitions (Dubinsky & Yiparaki, 2000).…”
Section: Task Sequencing In Definition-based Studiesmentioning
confidence: 99%
“…Moreover, defining tasks have varied considerably: some studies provided participants with a formal definition (Alcock & Simpson, 2011;Inglis & Simpson, 2008), some asked for a formal definition (Heinze & Kwak, 2002), some asked for something more akin to an explanation ('try to explain, in simple words. .…”
Section: Task Sequencing In Definition-based Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of legitimacy of this ultimate accomplishment is largely discussed in Vinner (1991). For Alcock and Simpson (2011), students do not necessarily feel the need for classifying a mathematical object as a member of a coherent set in which elements obey the same formal definition. They argue that before deciding on the use of a definition by students, it is important to investigate what they call concept consistency in order to consider student performance in the judgement of classification.…”
Section: Limitsmentioning
confidence: 99%